Waist circumference as a predictor for blood glucose levels in adults - Hardiman, Shinta L; Bernanthus, Intan Nevita; Rustati, Puspa K; Susiyanti, Eva (Faculty of Medicine, Trisakti University, 2009)
Anthropometric indexes such as body mass index (BMI), waist circumference (WC), hip ciucumference (HC), and waist–hip ratio (WHR), are all useful anthropometric measurements to provide important information on blood glucose concentrations. The aim of this study was to determine different anthropometric measurements, in particular BMI, waist circumference, hip circumference and waist-to-hip ratio, in their ability to predict the blood glucose levels in men and women 40 to 60. A cross-sectional study was conducted on a sample of 44 men and 127 women aged 40 to 50 who lived in Cipete Selatan subdistrict, South Jakarta. Blood glucose levels was assessed and anthropometric measurements comprising BMI, WC, HC, WHR were collected. Multiple linear regression analysis was used to determine the best predictor for blood glucose levels. The study showed that the prevalence of DM type 2 was 25.7% and the prevalence was higher in men (40.9%) compared to women (23.5%). The significant predictive variables in the simple regression analysis were age and waist circumference. Multiple linear regression showed that after adjustment for age, WC was positively associated with blood glucose levels. Standardized a value was 0.172 (p=0.026). WC predict blood glucose levels, beyond that explained by traditional diabetic risk factors and BMI. These findings provide support for the recommendation that WC be a routine measure for identification of diabetes mellitus type 2 in men and women aged 40 to 60 years.